Regional Disparities in the Prevalence and Severity of Early Childhood Caries Among Preschoolers Living in Poverty in Costa Rica - Gómez-Fernández, Adrián (2025)
Early childhood dental caries remains a major public health concern, especially among populations affected by socioeconomic and geographic disparities. In Costa Rica, persistent regional inequalities may influence the burden and severity of this condition. To analyze regional disparities in the prevalence and severity of dental caries among Costa Rican preschool children living in poverty. A secondary analysis was conducted using data from a descriptive, cross-sectional study carried out in 2013. The national sample included 803 children under 81 months of age enrolled in government-run centers for early childhood care and nutrition (CEN-CINAI). Clinical assessments were performed using the ICDAS system. Descriptive statistics and regional comparison tests were applied. The national caries prevalence in Costa Rica was 84.81%. Significant regional differences in severity were observed, with higher averages of affected teeth and surfaces in the Chorotega and Brunca regions. While incipient lesions (ICDAS 1-2) were most frequent, a substantial burden of moderate and severe lesions (ICDAS 3-6) was also detected, particularly in rural areas with greater structural vulnerability and limited access to oral health services.The high prevalence of dental caries and the documented regional inequalities highlight the need to strengthen prevention, early diagnosis, and timely treatment. Integrating a territorial approach into oral health policy-through early detection, preventive interventions, caregiver education, and mobile dental services-may help reduce disparities and improve pediatric oral health outcomes.